Hepatocyte growth factor can substitute for M-CSF to support osteoclastogenesis. - Adamopoulos, I; Xia, Z; Lau, Y; Athanasou, N (2006)
Osteopetrotic mice lacking functional macrophage-colony stimulating factor (M-CSF) recover with ageing, suggesting that alternative osteoclastogenesis pathways exist. Hepatocyte growth factor (HGF) and M-CSF signal through tyrosine kinase receptors and phosphorylate common transducers and effectors such as Src, Grb2, and PI3-Kinase. HGF is known to play a role in osteoclast formation, and in this study we have determined whether HGF could replace M-CSF to support human osteoclastogenesis. We found that the HGF receptor, c-Met, is expressed by the CD14(+) monocyte fraction of human peripheral blood mononuclear cells (PBMC). HGF was able to support monocyte-osteoclast differentiation in the presence of receptor activator for nuclear factor kappaB ligand as evidenced by the formation of numerous multinucleated tartrate-resistant acid phosphatase and vitronectin receptor positive cells which formed F-actin rings and were capable of lacunar resorption. The addition of a neutralising antibody to M-CSF did not inhibit osteoclast differentiation. HGF is a well-established survival factor and viability assays and live/dead staining showed that it promoted the survival and proliferation of monocytes and osteoclasts in a manner similar to M-CSF. Our findings indicate that HGF can substitute for M-CSF to support human osteoclast formation.